Critical Analysis of The Law on Purchasing Gold on Credit - Vivi Sylvia Purborini (LPPM Universitas Bina Taruna Gorontalo, 2024)
This study aims to understand the legal background of gold credit in Indonesia, we can explore more deeply how this product contributes to the development of Islamic banking, consumer protection, and financial market regulation more broadly. It also helps in identifying the challenges and opportunities faced in the implementation of Islamic financial practices in Indonesia. This writing uses a normative method where in this writing a literature search is conducted. Peter Mahmud stated that Legal Research must find a coherent truth, namely legal rules in accordance with legal norms or are there norms in the form of commands or prohibitions that are in accordance with Legal Principles and whether a person's actions are in accordance with Legal Principles or Legal Norms. Legal analysis of gold credit shows that this transaction involves various aspects that need to be considered, including the legal basis, sharia aspects (if applicable), financial risks, and legal treatment. It is important for financial institutions and customers to clearly understand their rights and obligations in gold credit contracts, and to comply with all applicable regulations to minimize risk and maintain fairness in this transaction.